FABRICATION AND CHARACTERIZATION OF DISSOLVING MICRONEEDLE PATCH USING 3D PRINTED MASTER - GUPTA, SHRADDHA; VASANTH, DHAKSHINAMOORTHY; KUMAR, AWANISH (International Journal of Applied Pharmaceutics, 2024)
Objective: The purpose of this study was to fabricate a dissolving microneedle patch using a 3D-printed master and characterize it using various techniques. Methods: Dissolving microneedle patches were developed using Computer-Aided Design (CAD) software and 3D printing. Polydimethylsiloxane (PDMS) reverse molds were cast from the 3D-printed masters and filled with a solution of 20% Chitosan Oligosaccharide (COS) and 20% Polyvinyl Alcohol (PVA). The patches were dried at room temperature and characterized using Scanning Electron Microscopy (SEM), Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR), X-ray diffraction (XRD), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), and in vitro skin penetration studies. Results: Optical microscopy and SEM images showed the formation of a uniform microneedle. The peak at 1248 cm⁻¹ in the ATR-FTIR spectrum indicates the formation of cross-links between certain PVA radical groups and COS. XRD revealed that both polymers blended well and showed partial crystallinity, with peaks at 2θ = 11.39°, 2θ = 20°, and 2θ = 41°. DSC and TGA analyses revealed that the blend could withstand high temperatures with good stability at temperatures up to 200 °C. In vitro skin penetration studies confirmed that microneedles could successfully penetrate the skin, indicating their potential for effective transdermal drug delivery. Conclusion: This study demonstrated that COS/PVA dissolving microneedles fabricated using 3D printing and micro-molding have significant potential for transdermal drug delivery.